2006
DOI: 10.1097/01.jcp.0000218985.07425.d9
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind, Placebo- and Flurazepam-controlled Investigation of the Residual Psychomotor and Cognitive Effects of Modified Release Zolpidem in Young Healthy Volunteers

Abstract: Short-acting hypnotic drugs, such as zolpidem, have minimal residual effects but may not provide optimal efficacy throughout the night for all insomnia patients. A modified-release formulation of zolpidem, zolpidem-MR, has been developed to overcome this limitation. This was a phase I, double-blind, 3-way crossover, placebo-controlled study to investigate the residual psychomotor and cognitive effects of a single oral dose of zolpidem-MR 12.5 mg in 18 healthy young adults. Flurazepam 30 mg was used as a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…36 We do not believe residual sedation accounts for the reduced SDMC with zolpidem-ER 12.5 mg. since testing was done 9.5 hours post-dose and studies of this drug as a hypnotic indicate no residual sedation 8.5 to 9.5 hours post dosing. 25,26,37 Although DSST scores with zolpidem-ER were slightly lower than those with zaleplon and placebo, follow-up correlational analyses between DSST and WPT/FTT performance showed no significant findings, indicating that any residual sedation present in the zolpidem-ER condition did not predict performance on the memory tests. We also visually examined the data to determine if residual sedation was more likely to occur in females, since the FDA has recently lowered the recommended dosage of zolpidem-ER for women based on reports that some women eliminate zolpidem more slowly than men.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…36 We do not believe residual sedation accounts for the reduced SDMC with zolpidem-ER 12.5 mg. since testing was done 9.5 hours post-dose and studies of this drug as a hypnotic indicate no residual sedation 8.5 to 9.5 hours post dosing. 25,26,37 Although DSST scores with zolpidem-ER were slightly lower than those with zaleplon and placebo, follow-up correlational analyses between DSST and WPT/FTT performance showed no significant findings, indicating that any residual sedation present in the zolpidem-ER condition did not predict performance on the memory tests. We also visually examined the data to determine if residual sedation was more likely to occur in females, since the FDA has recently lowered the recommended dosage of zolpidem-ER for women based on reports that some women eliminate zolpidem more slowly than men.…”
Section: Discussionmentioning
confidence: 85%
“…Zolpidem-ER has an estimated duration of action of 6-8 h, with a t 1/2 of 2.8 h and a t max of 1.5 h. 23 In contrast, zaleplon has an estimated duration of action of 3-4 h due to rapid absorption and elimination, with t 1/2 and t max both approximately one h. 24 These doses were chosen because, at the time of study, they were the recommended therapeutic doses for treatment of insomnia. In addition, residual morning sedation has not been detected with either drug at these doses when administered at bedtime, 25,26 or with zaleplon 10 mg when administered as little as 4 h before wake time (middle-of-the-night dosing). 27,28 Normal subjects were studied to avoid potential influence of the inherent sleep disruption of insomnia patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with prior research (cf. Blin et al, 2006). On the other hand, clinically significant sleep deficits have been associated with impaired cognitive abilities (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation consists of a 2-layer tablet that provides a biphasic release of zolpidem (immediate-release [IR], then slow-release) in the gastrointestinal tract. Several controlled studies have demonstrated the absence of residual effects of MR zolpidem at 8 hours postdose in elderly 27 and young healthy subjects 28 and in patients with insomnia. 24 A double-blind polysomnographic sleep study in normal volunteers utilized a model of sleep disruption through continuous exposure to pre-recorded traffic noise.…”
mentioning
confidence: 99%